Urgensi Pendirian BUMDes Untuk Mendorong Peningkatan UMKM dan Perekonomian Desa Sepulu Bangkalan - Ayu Lintang Priyan Andari; Nita Anggraini; Arista Widya Wulandari (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2025)
BUMDes is a business entity whose capital is wholly or largely owned by the village through direct participation originating from Village property which is separated to manage assets, services and other businesses for the greatest welfare of the Village community. The establishment of BUMDes aims to improve the village economy, improve the management of village potential and can also be a means of marketing local UMKM in Sepulu village because there are several UMKM in Sepulu village. However, several inhibiting factors were found in Sepulu village, namely the existence of internal factors. in the form of Human Resources, namely village communities who have not supported the establishment of BUMDes and the potential that exists in the village is not yet known for certain so this does not fulfill Article 213 of Law no. 32 of 2004 concerning Regional Regulations (hereinafter referred to as the Regional Regulation Law), this article explains that (1) villages can establish BUMDes in accordance with the needs and potential of the village